Spectroscopic Approach to Capillary-Alveolar Membrane Damage Induced Acute Lung Injury - Jing Wang; Luis Oppenheimer; Paola Fata; Julio Pintin; Ross Stimpson; Henry H Mantsch (Canadian Respiratory Journal)
BACKGROUND: Acute (or adult) respiratory distress syndrome (ARDS) is often associated with a high mortality rate in the critical care population. The term acute lung injury (ALI), a primitive phase of ARDS, was introduced by the European and American consensus groups to provide early diagnoses of ARDS. The pathophysiological characterization of ALI/ARDS – an increased pulmonary capillary-alveolar membrane barrier permeability – is generally not included in current intensive care unit diagnosis criteria.